A Temporal and spatial Study of the variations of total abundance of values for Ichtyoplankton and zooplankton dynamics in Syrian northern coastal waters (Latakia University Journal -Biological Sciences Series, 2019)
جمعت 66 عينة من العوالق السمكية والعوالق الحيوانية باستخدام شبكة بلانكتونية  WP2 قطر ثقوبها 350 ميكرون بشكل دوري وبطريقة الجمع الأفقي من ثلاثة مواقع: برج إسلام، وادي قنديل وأم الطيور ومن محطتين في كل موقع (الأولى  قريبة من الشاطئ والثانية بعيدة عنه) تختلف بخصائصها البيئية، وذلك على امتداد 15كم2 تقريباً، كما تم قياس درجة الحرارة والملوحة والحموضة لـ. 264 عينة خلال الفترة الواقعة بين 12\5\2009 و 12\1\2011. أثبتت نتائج الدراسة وجود تغيّرات زمانية ومكانية في توزع و غزارة العوالق السمكية والعوالق الحيوانية وكانت منطقة برج إسلام أكثر غنىً بقيم غزارة اليرقات السمكية (9,40فرد\1000م3) تلتها منطقة وادي قنديل ثم منطقة أم الطيور بمتوسط 4.70 فرد\1000م3 لكل منهما، وكانت مياه المنطقة القريبة من الشاطئ أكثر غزارة من تلك البعيدة عنه. كما تم خلال الدراسة تحديد مدى تأثير عدد من العوامل الهيدرولوجية وكذلك غزارة العوالق الحيوانية على حركية العوالق السمكية في مواقع الدراسة، وكان تأثير درجة الحرارة أكثر أهمية من العوامل البيئية الأخرى. 66 samples of Ichthyoplankton and zooplankton were carried out by WP2 net with mesh size 350µm as periodicity were done using horizontal collection method from three locations; Berj-Islam, Wadi-Kandeel and Am-Attiyor with two stations chosen from each location (inshore-offshore) to represent different environments and extending nearly 15k.m2, temperature, salinity and pH were measured for 264 samples during the period between 12.5.2009 and 12.1.2011. According to the present results, temporal and spatial variations distribution and abundance of Ichthyoplankton and zooplankton were observed. More abundant of fish larva was found at Berj-Islam (9.40 individuals\1000m3), followed by Wadi-Kandeel and Am-Altyor with mean 4.70 individuals\1000m3 for each, conclude that fish larva were more abundant at the inshore than offshore water stations. Also, the effect of some hydrological parameters and zooplankton abundance on monitoring of Ichthyoplankton were detected along locations, temperature factor was more significant than other parameters.